2017
DOI: 10.1055/s-0037-1604274
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Texts in Interactive Reading Activities for Children with Language Delays and Disorders: A Review of the Research Literature and Pilot Study

Abstract: Participation in interactive reading activities can help children with language delays and disorders build important early language and literacy skills. Digital texts (i.e., books presented on tablets and computers) provide new opportunities for learning and supporting communication. Recently, researchers have investigated the use of digital texts that include visual scene displays (VSDs). In this approach, pictures on a tablet are programmed with “hotspots”; when the picture is touched, a word is spoken aloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The focus of the meta-analysis was on studies that reported quantitative comparisons of reading a paper and digital version of the same story. We therefore excluded (1) studies without a control group (e.g., Klop et al, 2018;Messier & Wood, 2015) and case studies (e.g., Boyle et al, 2017, making use of a single-case multiple baseline across participants design); (2) studies that included comparisons between paper on the one hand and video, an audio story, or a film on the other hand were excluded (e.g., Meringoff, 1980); (3) apart from studies just focusing on behavior during book reading (e.g., Moody et al, 2010;Rees et al, 2017) we did not include studies targeting basic reading skills such as letter knowledge or phonemic awareness (e.g., Evans et al, 2017;Segal-Drori et al, 2010;Willoughby et al, 2015) or recognition of kana characters (e.g., Masataka, 2014); (4) we also excluded studies targeting participants older than 8 years (e.g., Connor et al, 2019) and participants with Cochlear implants (e.g., Messier & Wood, 2015) or diagnosed with autism (e.g., Wainwright et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The focus of the meta-analysis was on studies that reported quantitative comparisons of reading a paper and digital version of the same story. We therefore excluded (1) studies without a control group (e.g., Klop et al, 2018;Messier & Wood, 2015) and case studies (e.g., Boyle et al, 2017, making use of a single-case multiple baseline across participants design); (2) studies that included comparisons between paper on the one hand and video, an audio story, or a film on the other hand were excluded (e.g., Meringoff, 1980); (3) apart from studies just focusing on behavior during book reading (e.g., Moody et al, 2010;Rees et al, 2017) we did not include studies targeting basic reading skills such as letter knowledge or phonemic awareness (e.g., Evans et al, 2017;Segal-Drori et al, 2010;Willoughby et al, 2015) or recognition of kana characters (e.g., Masataka, 2014); (4) we also excluded studies targeting participants older than 8 years (e.g., Connor et al, 2019) and participants with Cochlear implants (e.g., Messier & Wood, 2015) or diagnosed with autism (e.g., Wainwright et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Further research on the effects of AAC interventions on academic skills was recommended by 4 reviews (Ganz et al, 2014a;Ganz et al, 2017;Hong et al, 2017;Still et al, 2014). Other reviews recommended further research on the impact of technology aided instruction on literacy outcomes (Barker et al, 2012;Boyle et al, 2017;Machalicek et al, 2010;Stauter et al, 2017).…”
Section: Reviewmentioning
confidence: 99%
“…With the T2L feature, upon selection of a hotspot in the VSD, the written word appears dynamically and is then spoken out (https://tinyurl.com/rerc-on-aac-T2L). A number of studies have shown that individuals with developmental disabilities have successfully acquired sight words, without explicit instruction, when introduced to an AAC app utilizing VSDs with the T2L feature; these results have been demonstrated with young children with ASD (Mandak, Light, & McNaughton, 2018), adults with severe intellectual developmental disabilities (Holyfield, Light, McNaughton, Pope, & Drager, 2018), and young children with communication impairments participating in small group activities with their typical peers (Boyle, McCoy, McNaughton, & Light, 2017). It should be noted that the T2L feature includes other components besides motion and it is not possible to tease out the relative contributions of each component.…”
Section: Designing Effective Visual Scene Displaysmentioning
confidence: 99%